Prevalence and Risk Factors of Iron Deficiency Anemia among Postpartum Women - Darmawati Darmawati; Syahbandi Syahbandi; Aida Fitri; Masyithah Audina (Universitas Padjadjaran, 2020)
One of the problems that contributes to the highest number of maternal mortality and morbidity is postpartum anemia. It is estimated that 50–80% of women experience anemia within 48 hours after giving birth. Globally, the commonest cause of anemia is iron deficiency. In Aceh, study on anemia in the postpartum period is still rare and requires to get more attention. This study aims to identify the prevalence of anemia among postpartum women and the associated risk factors that influence the incidence of postpartum iron deficiency anemia. This study is a quantitative study with a cross-sectional study design conducted at dr. Zainoel Abidin Hospital. Participants in this study were recruited using a non-probability sampling method and obtained 102 participants. Data were analyzed using chi-square tests with a confidence level of 95%. This study showed that 49.0% of the postpartum women had mild anemia, 10.8% of them had moderate anemia, and another 40.2% do not have anemia. It is found that there is a significant relationship between obstetric factors (type of labor, delivery complications) with anemia among anemia postpartum mothers ( .014 and .047 respectively).